(untitled) (Journal of Ideas in Health, 2021)
Background: Elderly constitutes a vulnerable group for depression, as they are especially prone to suffer adverse consequences of a depressive episode and have greater rates of completed suicides. This study aims to estimate the prevalence and determinants of geriatric depression. Methods: A cross-sectional study was done among 250 elderlies from 1st January 2019 to 1st January 2020 in the different rural blocks of Ernakulam district, India. The multistage sampling technique and the Geriatric Depression Scale (GDS-30) were used to collect the data. A score of 0 9 is considered "normal", 10 19 is labeled as "mildly depressed", and 20 30 as "severely depressed". Statistical analysis was performed using the IBM SPSS software. The Chi-square test /Fisher’s exact test was used to study the association between the socio-demographic and behavioral variables with depression. Results: The mean age was 69.33 ± 7.41years and male: female ratio was 0.55: 1.The overall prevalence of depression was 52.4%. Advanced age over 70years [OR=2.04;95% CI, 1.227 – 3.394; P=0.006], female gender[OR=2.844;95% CI,1.663-4.865; P =<0.001], lack of gainful employment [OR=3.504; 95% CI, 1.833–6.699; P =<0.001], physical dependence [OR=0.365;95% CI,0.162–0.821; P =0.012], financial dependence [OR=0.388; 95% CI, 0.219–0.687; P =<0.001], presence of medical co morbidities [OR=0.428; 95% CI, 0.212–0.866; P =0.016],poor lifestyle including the lack of regular exercise [OR =2.020; 95% CI,1.174–3.473; P =0.010], addiction to alcohol [OR=4.932;95%CI,1.600-15.208; P =0.004] and addiction to tobacco smoking [OR=2.905;95%CI,1.273-6.628; P =0.009] and poor family support [OR= 5.180;95% CI,716–15.636; P = 0.002] were found to be significantly associated with depression. Conclusion: The prevalence of depression among the elderlies was high, and hence early diagnosis and prompt treatment are essential to reduce its burden in the community.